Stimulants and performance - Wagner, J. C.
Much of the earliest performance drug use in athletics involved stimulants. In the late nineteenth century European cyclists reportedly consumed a number of concoctions to reduce fatigue. Prior to competition athletes would take caffeine-based sugar cubes that had been dipped in nitroglycerin or a drink called vin mariani, that was a combination of wine and coca leaves. In the modern era of sports, these crude preparations had been replaced with more powerful stimulants, most notably amphetamine. Stimulant use was suspected initially during the Summer and Winter Olympic Games in 1952. Amphetamine use was blamed for the deaths of two elite cyclists, one during the 1960 Summer Olympics in Rome and the other during the 1967 Tour de France. Shortly thereafter, the use of amphetamines, or "pep pills" by professional athletes was exposed. Epidemiology As with most performance drug use, few epidemiological studies have been conducted that define the magnitude of the problem. The most comprehensive work to date has been from a team of researchers at Michigan State University College of Human Medicine who have looked at drug use among a broad cross-section of student-athletes at National Collegiate Athletic Association (NCAA) institutions. The survey, which was conducted initially in 1985 and repeated in 1989, shows that during that time period amphetamine drug by athletes dropped from 8% to 2%. The use of weight loss products, many of which are stimulants, was not studied in 1985 but in 1989 five percent of respondents indicated that they used these substances. Caffeine use was virtually unchanged (68% in 1985 down to 64% in 1989) and cocaine/crack use fell dramatically from 17% to 4% over the same period. An important and potentially troubling result from the same study was that 22% of respondents indicated that the source of amphetamines was a representative of the athletic department (coach, trainer or team physician). In 1985 only 4% of respondents identified this group of individuals as their source for amphetamines. This finding was a notable exception to the trend of obtaining ergogenic drugs outside of the athletic department. Mandell and colleagues studied the usage rates of amphetamines by National Football League teams. Purchase records from 1968 and 1969 revealed that approximately 65 amphetamine tablets per player per game were used by NFL teams. Subsequent interviews with 87 players from eleven different teams suggested that two-thirds of professional football players use these drugs occasionally and more than half were regular users. Dosages used varied by position and ranged from 5 to 150 mg per game. Certain sports, such as gymnastics and wrestling as well as ballet dance require weight control. Participants in these activities may be at an increased risk for eating disorders and therefore amphetamine abuse. Amphetamine - Caffeine - Cocaine